RUMAH GADANG DAN NILAI –NILAI KEARIFAN LOKAL DALAM KEBUDAYAAN MINANGKABAU DI TANAH DATAR - Dwi Chintya Ramadika; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Local wisdom has its own form or form, the form of local wisdom can be categorized into two aspects, namely tangible and intangible local wisdom. In this regard the researcher discusses the local wisdom and values contained in Rumah Gadang in West Sumatra. Minangkabau traditional house is called Rumah Gadang or Rumah Godang which is the result of local wisdom of the people of West Sumatra. Rumah Gadang which is a traditional house and found in many provinces of West Sumatra, Indonesia. The purpose of this research is to know the meaning of the philosophy that is contained in the carvings, shapes and colors of Rumah Gadang, the function of Rumah Gadang and to know the public perception of the existence of Rumah Gadang in Tanah Datar regency of West Sumatra. The method used in this research is histori and descriptive method. Data obtained through literature techniques, documentation and comparative studies. while the research location is in Tanah Datar regency of West Sumatra. The time of study counted from the start of the proposal results seminar until the test results. The result of this research is that the Minangkabau community is a dynamic society that will always change with the passage of time. As it has been rung in one of the Minangkabau adage proverb namely 'Alam Takambang Jadi Guru'. One interesting thing that we can conclude here is that every lesson learned from nature should be able to be accumulated as new inputs in life, even this is not covered in terms of their homes or residential facilities.Keywords : Rumah Gadang, Values of Local Wisdom, Minangkabau Cultur